2020
DOI: 10.3390/pathogens9020095
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella enterica Isolates from Diseased Poultry in Northern China between 2014 and 2018

Abstract: Salmonella infection not only causes acute and chronic diseases in poultry flocks, but the infected poultry are among the most important reservoirs for a variety of Salmonella serovars frequently transmitted to humans. This study aimed to investigate the occurrence of Salmonella spp. in local poultry farms in China. Samples (n = 4255), including dead-in-shell embryos, culled day-old-hatchings and 1- to 4-week-old diseased birds, were collected for Salmonella culture from broiler chicken, meat-type duck and pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 46 publications
4
41
2
Order By: Relevance
“…The most prevalent Salmonella serovars are including S. Typhimurium, S. Enteritidis, S . Pullorum and S. Gallinarum, among them, S. Typhimurium and S. Enteritidis have been described as worldwide spread [ 1 , 2 , 3 ]. Some of these prevalent serovars could lead to serious zoonotic diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent Salmonella serovars are including S. Typhimurium, S. Enteritidis, S . Pullorum and S. Gallinarum, among them, S. Typhimurium and S. Enteritidis have been described as worldwide spread [ 1 , 2 , 3 ]. Some of these prevalent serovars could lead to serious zoonotic diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…indicated that all isolated Salmonella strains exhibited absolute resistance (100%) against Trimethoprim-Sulfamethoxazole, indicating the limited therapeutic value of this antibiotic to poultry [45], In the current study chicks showed high resistance to Clindamycin and Lincomycin 100% and variable resistance to Trimethoprim-sulfamethoxazole 50% then Tetracycline, Ampicillin and Ciprofloxacin 33%. [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…All of the 47 samples analyzed by the classical serotyping slide agglutination test comprising of food (7), chicken meat (11) and chicken cloacal swab (29), in accordance with the White-Kauffmann-Le Minor scheme and only isolates belonging to the Salmonella enterica Enteritidis serotype were selected for this study. Based on the phenotypic antimicrobial resistance pattern of the isolates against the nine (9) different antimicrobial drugs, 27 (57.45%) of the isolates were found to show resistance to 1 or more antimicrobials tested (Table 1).…”
Section: Serotyping Of Salmonella and Antimicrobial Resistancementioning
confidence: 99%
“…It is based on the principle of the multi-locus enzyme electrophoresis that uses a combination of discriminatory power and clonal stability, which has proven to be extremely efficient in characterizing clones within a population of bacterial organisms causing serious disease [10]. However, it uses allelic differences in the sequence of various house-keeping genes that are often exploited to differentiate strains (Wang, & Su, 2020). In this investigation, the phenotypic antimicrobial resistance profile and molecular characteristics of Salmonella enterica serovar Enteritidis isolated from chicken and food samples was assessed to determine the antimicrobial resistance variability and distribution.…”
Section: Introductionmentioning
confidence: 99%